The impact of flipped learning strategy according to sensory modelling in learning the skills of passing and dribbling in football for students (Journal of Humanities and Social Sciences Research, 2023)
Using the flipped learning method according to (sensory modelling) in the learning process to excite the learner and continue performance growth via the best use of visual and aural means that represent him with sensory modelling in the sports field. In addition to decreasing the teacher's work and time and improving the learner's information. The study aims to determine the influence of an inverted learning technique based on sensory modelling on students' learning of passing and dribbling football abilities. Two equal groups were utilized in the experiment (experimental and control). The research community was chosen by the students of the first stage at Dhi Qar University's College of Physical Education and Sports Sciences for the academic year (2021-2022), which totalled (96) individuals. The primary experiment sample was randomly chosen and consisted of (30) students divided equally into two groups, experimental and control, with each group consisting of (15) individuals. The primary sample was tested on dribbling and dribbling in football in the before and post-test, and the instructional modules were used using the flipped learning technique based on sensory modelling for (8) weeks. It consisted of (16) instructional units, with two weekly units for two days (Tuesday and Thursday). One of the study's most significant findings was that the flipped learning technique based on sensory modelling improved the student’s performance level in the two football abilities (passing and rolling). In addition, the sensory modelling-based flipped learning technique assisted me in understanding and consolidating material relevant to my football abilities (passing, and dribbling). One of the most important recommendations recommended by the researchers is the need to use the flipped learning strategy according to sensory modelling to raise the level of skill performance in football for students and the need to encourage teachers to use the flipped learning strategy according to sensory modelling and adopt it in teaching various subjects.